Research on Explosives Detection Technologies in Aviation Security Industry - Asgarov, K.A.; Mukhtarov, R.M.; Ahmadova, S.T. (Herald of Azerbaijan Engineering Academy, 2024)
The article provides practical knowledge about the explosives detection research. Also, the application characteristics of the device for the detection of explosive substances are defined. Currently, among the special means of ensuring aviation security, X-ray television intro scopes are most widespread due to their high speed of inspection and the ability to detect bladed weapons and firearms, as well as detect explosives and explosive devices. However, conventional X-ray inspection systems cannot separate explosives from harmless substances with decision to the operator. The latter circumstance leads to a significant dependence of the quality of inspection on the experience and qualifications of the operator.